Observation of stimulated Brillouin scattering in silica graded‐index multimode optical fibre based on pump‐probe technique. Issue 5 (1st February 2013) - Hayashi, N.; Mizuno, Y.; Nakamura, K.
Abstract : Based on the pump‐probe technique (PPT), stimulated Brillouin scattering (SBS) was observed in a 100 m‐long silica graded‐index multimode optical fibre with the same core diameter as that of a perfluorinated graded‐index polymer optical fibre (PFGI‐POF) (=50 µm). The SBS threshold was measured to be ∼50 mW, which was much lower than 5.08 W, the SBS threshold obtained for the same fibre without the PPT. This result indicates that the PPT is useful even under multimode conditions and that the difficulty in observing SBS in PFGI‐POFs consists not in their physical problems but in their material problems (high propagation loss etc.).